Ultrahigh-burning-rate double-layer ignition sheet as well as preparation method and application thereof

By adopting a double-layer structure of ultra-high combustion speed Al-Ni film and main ignition layer in the thermal battery ignition film, the problem of insufficient combustion speed of the existing ignition film is solved, and the activation time of the thermal battery is significantly shortened and the output of the thermal battery is achieved. Power increase.

CN119495759APending Publication Date: 2025-02-21GUIZHOU MEILING POWER SUPPLY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411682179.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing thermal battery ignition plates have insufficient combustion speed and cannot meet the requirements of high-performance thermal batteries for activation time and output power.

Method used

Using a double-layer structure ignition sheet with ultra-high combustion speed Al-Ni film and main ignition layer, it is prepared by spraying a mixture of micro-nano aluminum powder and micro-nano nickel powder on asbestos paper and drying in argon protective gas, combined with The main ignition layer of zirconium powder, barium chromate and loose asbestos form an efficient combustion system.

Benefits of technology

The combustion speed of the ignition plate is increased to 6-8m/s, which significantly shortens the activation time of the thermal battery, improves the ignition success rate and output power, and reduces the risk of combustion energy and powder splashing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495759A_ABST
    Figure CN119495759A_ABST
Patent Text Reader

Abstract

The invention discloses an ultrahigh-burning-speed double-layer ignition sheet in the technical field of thermal batteries, and the ultrahigh-burning-speed double-layer ignition sheet is prepared by the following steps: step 1, slurry preparation: using distilled water to immerse loose asbestos paper until the loose asbestos paper is soft, then crushing the loose asbestos paper, adding zirconium powder, and uniformly mixing to obtain a zirconium powder paper pulp solution; respectively adding barium chloride and potassium chromate into the zirconium powder paper pulp solution in a stirring state to obtain a turbid liquid containing the loose asbestos, the zirconium powder and the barium chromate, performing suction filtration to obtain a mixture containing the barium chromate, the zirconium powder and the loose asbestos, dispersing the mixture in an adhesive, and uniformly stirring to obtain slurry; wherein the mass ratio of the loose asbestos to the barium chloride to the zirconium powder to the potassium chromate is (1-10): (35-45): (15-20): (25-35); and secondly, the slurry prepared in the first step is sprayed on an ultra-high-burning-rate Al-Ni film, drying is conducted for 1.5-2.5 h under the condition of 120-180 DEG C in argon shielding gas, and the ultra-high-burning-rate double-layer ignition sheet is obtained. Compared with the prior art, the ultrahigh-burning-speed double-layer ignition sheet prepared by the invention is higher in burning speed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal batteries, and in particular relates to an ultra-high burning rate double-layer ignition sheet and a preparation method and application thereof. Background Art

[0002] Thermal battery is a heat-activated reserve battery that relies on its own heating system to heat and melt non-conductive solid salt electrolytes into ionic conductors to enter the working state. Thermal batteries have the characteristics of activation at any angle, fast activation speed, long storage time, and strong ability to withstand environmental mechanical conditions. They have been widely used in aerospace equipment. In addition, the application of thermal batteries in the civilian field has also been valued and has been used as aircraft emergency power supply, fire alarm power supply, and underground high-temperature prospecting power supply.

[0003] With the continuous development and updating of aerospace equipment, the requirements for the performance of thermal batteries are getting higher and higher, and the requirements for their working time, output power, and high specific characteristics are getting higher and higher, and the activation time is getting faster and faster. Thermal batteries are mainly composed of substrates, positive electrodes, negative electrodes, electrolyte sheets (or diaphragm sheets), sheet current collectors, heating systems (electric ignition heads or flames, ignition paper, heating sheets), insulation pads, battery shells, and battery covers with terminals. Factors that affect the activation time of the battery include the detonation time of the electric ignition head, the burning speed of the ignition sheet, the ignition time of the heating sheet, and the melting time of the electrolyte. Increasing the burning speed of the ignition sheet can greatly increase the battery activation time.

[0004] For example, the patent with publication number "CN 113322115 A" discloses a thermal battery composite ignition paper and its preparation method. The composite ignition paper has a double-layer structure, which is divided into an ignition paper layer and a combustion-supporting layer, which are bonded together. The ignition paper layer is zirconium-barium chromate-potassium perchlorate type ignition paper, and the combustion-supporting layer is aluminum foil, aluminum oxide sheet, mica sheet or kraft paper, etc. Compared with conventional ignition paper, the composite ignition paper provided by the invention has a greatly improved ignition paper line burning speed of 200-450cm / s, but there is still room for further improvement. Summary of the invention

[0005] The present invention aims to provide a double-layer ignition sheet with ultra-high burning speed to improve its burning speed.

[0006] An ultra-high burning rate double-layer ignition sheet in the present scheme comprises an ultra-high burning rate Al-Ni film and a main ignition layer attached to the ultra-high burning rate Al-Ni film, wherein the mass ratio of Al-Ni in the ultra-high burning rate Al-Ni film is 0.45-1.38:1.

[0007] Furthermore, the ultra-high burning rate Al-Ni film is prepared by the following method: dispersing micro-nano aluminum powder and micro-nano nickel powder in a PVB solution, stirring evenly to obtain a mixture, then spraying it on asbestos paper, and finally drying to obtain an ultra-high burning rate Al-Ni film; wherein the PVB:ethanol in the PVB solution is 1g:90-120ml; the mass ratio of the sum of the mass of the micro-nano aluminum powder and the micro-nano nickel powder to the mass of the PVB solution is 0.9-1.1:1.

[0008] Furthermore, when preparing the ultra-high burning rate Al-Ni film, the spraying thickness of the mixture on the asbestos paper is 20-100 um.

[0009] Furthermore, the raw materials of the main ignition layer include zirconium powder, barium chromate, loose asbestos paper and adhesive.

[0010] Furthermore, the thickness of the main ignition layer is 100um-200um.

[0011] The method for preparing the ultra-high burning rate double-layer ignition sheet comprises the following steps:

[0012] Step 1, preparation of slurry: using distilled water to immerse the loose asbestos paper and soak it until it is soft, then crushing the loose asbestos paper and adding zirconium powder, mixing to obtain a zirconium powder pulp solution; adding barium chloride and potassium chromate to the zirconium powder pulp solution under stirring to obtain a suspension containing loose asbestos, zirconium powder and barium chromate, filtering to obtain a mixture containing barium chromate, zirconium powder and loose asbestos, dispersing the mixture in an adhesive and stirring evenly to obtain a slurry; wherein the mass ratio of loose asbestos, barium chloride, zirconium powder and potassium chromate is 1-10:35-45:15-20:25-35;

[0013] Step 2: spray the slurry prepared in step 1 on the ultra-high burning rate Al-Ni film, and dry it in argon protective gas at 120-180° C. for 1.5-2.5 hours to obtain the ultra-high burning rate double-layer ignition sheet.

[0014] Furthermore, the adhesive is a PVB solution.

[0015] Furthermore, the ratio of PVB to ethanol in the PVB solution is 1 g:90-120 ml.

[0016] Furthermore, when preparing the slurry, the mass ratio of the mixture to the PVB solution is 0.9-1.1:1.

[0017] Beneficial effects:

[0018] 1. The ultra-high burning rate double-layer ignition sheet prepared by the present invention can give full play to the advantages of their respective raw materials. The ultra-high burning rate double-layer ignition sheet material has a burning rate of 6-8m / s, which can greatly shorten the activation time of the thermal battery.

[0019] 2. The combustion energy is moderate, the ignition success rate is high, and the heating plate can be ignited quickly; the ignition point is above 400℃, the ignition sensitivity is low, and the probability of accidental ignition due to friction and impact is low.

[0020] 3. The preparation process is simple, the operability is strong, the equipment cost is low, and it is conducive to large-scale production. Compared with traditional fast ignition materials, the thermal shock is relatively small, and there is less powder splashing during the combustion process;

[0021] Based on the excellent performance of the above-mentioned ultra-high burning rate double-layer ignition sheet, it can be widely used in thermal batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Attached Figure 1 This is a physical picture of the ultra-high burning rate double-layer ignition sheet prepared in Example 1 of the present invention;

[0023] Attached Figure 2 The figure is a comparison chart of the activation time of a thermal battery including the ultra-high burning rate double-layer ignition sheet of Example 1 and a thermal battery including an ignition sheet in the prior art. DETAILED DESCRIPTION

[0024] The following is further described in detail through specific implementation methods:

[0025] Example 1

[0026] The preparation of the ultra-high burning rate double-layer ignition sheet comprises the following steps:

[0027] 1) Disperse micro-nano aluminum powder and micro-nano nickel powder in PVB solution (PVB: ethanol = 1g: 100ml), the mass ratio of micro-nano aluminum powder to micro-nano nickel powder is 1:1; the mass ratio of the sum of the mass of micro-nano aluminum powder and micro-nano nickel powder to the PVB solution is 1:1, stir evenly and spray on asbestos paper, control the thickness of the spray layer to 60um, and finally dry at 80°C for 4h to obtain an ultra-high burning rate Al-Ni film.

[0028] 2) Using distilled water to immerse the loose asbestos paper and soak it until it is soft, then crushing the loose asbestos paper and adding zirconium powder, mixing to obtain a zirconium powder pulp solution, adding barium chloride and potassium chromate to the zirconium powder pulp solution under stirring, respectively, to obtain a suspension containing loose asbestos, zirconium powder and barium chromate, the ratio of loose asbestos, barium chloride, zirconium powder and potassium chromate is 5:38:18:30; filtering to obtain a mixture containing barium chromate, loose asbestos and zirconium powder, dispersing the mixture in a PVB solution and stirring evenly to obtain a slurry; PVB:ethanol in the PVB solution is 1g:100ml, and the mass ratio of the mixture to the PVB solution is 1:1.

[0029] 3) Spray the slurry prepared in step 2) on the ultra-high burning rate Al-Ni film substrate prepared in step 1), and control the spraying thickness to 150um. Finally, dry it at 150°C for 2h in argon protective gas to obtain an ultra-high burning rate double-layer ignition sheet, as shown in the attached Figure 1 shown.

[0030] Example 2

[0031] The preparation of the ultra-high burning rate double-layer ignition sheet comprises the following steps:

[0032] 1) Disperse micro-nano aluminum powder and micro-nano nickel powder in PVB solution (PVB: ethanol = 1g: 100ml), the mass ratio of micro-nano aluminum powder to micro-nano nickel powder is 1:1; the mass ratio of the sum of the mass of micro-nano aluminum powder and micro-nano nickel powder to the PVB solution is 1:1, stir evenly and spray on asbestos paper, control the thickness of the spray layer to 80um, and finally dry at 60°C for 5h to obtain an ultra-high burning rate Al-Ni film.

[0033] 2) using distilled water to immerse the loose asbestos paper and soak it until it is soft, then crushing the loose asbestos paper and adding zirconium powder, mixing to obtain a zirconium powder pulp solution, adding barium chloride and potassium chromate to the zirconium powder pulp solution under stirring, respectively, to obtain a suspension containing loose asbestos, zirconium powder and barium chromate, the ratio of loose asbestos, barium chloride, zirconium powder and potassium chromate is 5:38:18:30, filtering to obtain a mixture containing barium chromate, loose asbestos and zirconium powder, dispersing the mixture in the PVB solution and stirring evenly to obtain a slurry; the PVB:ethanol in the PVB solution is 1g:100ml, and the mass ratio of the mixture to the PVB solution is 1:1;

[0034] 3) Spray the slurry prepared in step 2) on the ultra-high burning rate Al-Ni film substrate prepared in step 1), and the spraying thickness is controlled at 150um. Finally, dry it at 150°C for 2h in argon protective gas to obtain an ultra-high burning rate double-layer ignition sheet after drying.

[0035] Example 3

[0036] The preparation of the ultra-high burning rate double-layer ignition sheet comprises the following steps:

[0037] 1) Disperse micro-nano aluminum powder and micro-nano nickel powder in PVB solution (PVB: ethanol = 1g: 100ml), the mass ratio of micro-nano aluminum powder to micro-nano nickel powder is 1:1; the mass ratio of the sum of the mass of micro-nano aluminum powder and micro-nano nickel powder to the PVB solution is 1:1, stir evenly and spray on asbestos paper, control the thickness of the spray layer to 40um, and finally dry at 100°C for 3h to obtain an ultra-high burning rate Al-Ni film.

[0038] 2) using distilled water to immerse the loose asbestos paper and soak it until it is soft, then crushing the loose asbestos paper and adding zirconium powder, mixing to obtain a zirconium powder pulp solution, adding barium chloride and potassium chromate to the zirconium powder pulp solution under stirring, respectively, to obtain a suspension containing loose asbestos, zirconium powder and barium chromate, the ratio of loose asbestos, barium chloride, zirconium powder and potassium chromate is 5:38:18:30, filtering to obtain a mixture containing barium chromate, loose asbestos and zirconium powder, dispersing the mixture in the PVB solution and stirring evenly to obtain a slurry; the PVB:ethanol in the PVB solution is 1g:100ml, and the mass ratio of the mixture to the PVB solution is 1:1;

[0039] 3) Spray the slurry prepared in step 2) on the ultra-high burning rate Al-Ni film substrate prepared in step 1), and control the spraying thickness to 120um. Finally, dry it at 150°C for 2h in argon protective gas to obtain an ultra-high burning rate double-layer ignition sheet.

[0040] Experimental comparison

[0041] In the following text, the ignition paper conventionally prepared by the company refers to the ignition sheet prepared using the patented technology with authorization announcement number "CN 109837806 B" (Example 3); CN 113322115 A ignition paper refers to the ignition sheet prepared using the patented technology with publication number "CN113322115A" (Example 5).

[0042] The ignition pieces prepared in Example 1 (this patent) and the prior art (the company's conventional technology, CN 113322115 A patent technology) were assembled into unit cells of the same specifications for electrical performance testing. The test results are shown in the attached figure. Figure 2 As shown in the attached Figure 2 It can be seen that the activation time of the same size thermal batteries assembled from the ignition paper prepared by this patent technology, the company's conventional technology and the CN 113322115 A patent technology are 28ms, 36ms and 54ms respectively, indicating that the activation time of the unit thermal battery of the high burning rate double-layer ignition sheet prepared in Example 1 is greatly shortened.

[0043] In addition, four samples of the ignition sheets prepared in Examples 1 to 3, CN 109837806 B (Example 3), and CN 113322115 A (Example 5) were taken for burning rate test. The test results are shown in the following table:

[0044] Group No. 1 No. 2 No. 3 No. 4 Example 1 650.0cm / s 631.2cm / s 654.2cm / s 635.3cm / s Example 2 710.8cm / s 720.5cm / s 700.6cm / s 718.6cm / s Example 3 618.5cm / s 624.3cm / s 635.2cm / s 628.7cm / s CN109837806B 59.6cm / s 53.7cm / s 61.5cm / s 58.3cm / s CN113322115A 416.3cm / s 412.5cm / s 398.6cm / s 398.4cm / s

[0045] It can be seen from the above table that the ultra-high burning rate double-layer ignition sheet prepared in the present application has a higher burning rate.

[0046] The above is only an embodiment of the present invention, and the common knowledge such as the known specific structure and characteristics in the scheme is not described in detail here. It should be pointed out that for those skilled in the art, several deformations and improvements can be made without departing from the structure of the present invention, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. An ultra-high burning rate double-layer ignition sheet, characterized in that: The invention comprises an ultra-high burning rate Al-Ni film and a main ignition layer attached to the ultra-high burning rate Al-Ni film. In the ultra-high burning rate Al-Ni film, the mass ratio of Al-Ni is 0.45-1.38:

1.

2. The ultra-high burning rate double-layer ignition sheet according to claim 1, characterized in that: The ultra-high burning rate Al-Ni film is prepared by the following method: dispersing micro-nano aluminum powder and micro-nano nickel powder in a PVB solution, stirring evenly to obtain a mixture, then spraying it on asbestos paper with a spraying thickness of 20-100um, and finally drying to obtain the ultra-high burning rate Al-Ni film; wherein the PVB:ethanol in the PVB solution is 1g:90-120ml; and the mass ratio of the sum of the mass of the micro-nano aluminum powder and the micro-nano nickel powder to the mass of the PVB solution is 0.9-1.1:

1.

3. The ultra-high burning rate double-layer ignition sheet according to claim 2, characterized in that: When preparing the ultra-high burning rate Al-Ni film, the spraying thickness of the mixture on the asbestos paper is 20-100um.

4. The ultra-high burning rate double-layer ignition sheet according to claim 3, characterized in that: The raw materials of the main ignition layer include zirconium powder, barium chromate, loose asbestos paper and adhesive.

5. The ultra-high burning rate double-layer ignition sheet according to claim 4, characterized in that: The thickness of the main ignition layer is 100um-200um.

6. The method for preparing the ultra-high burning rate double-layer ignition sheet according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1, preparation of slurry: using distilled water to immerse the loose asbestos paper and soak it until it is soft, then crushing the loose asbestos paper and adding zirconium powder, mixing to obtain a zirconium powder pulp solution; adding barium chloride and potassium chromate to the zirconium powder pulp solution under stirring to obtain a suspension containing loose asbestos, zirconium powder and barium chromate, filtering to obtain a mixture containing barium chromate, zirconium powder and loose asbestos, dispersing the mixture in an adhesive and stirring evenly to obtain a slurry; wherein the mass ratio of loose asbestos, barium chloride, zirconium powder and potassium chromate is 1-10:35-45:15-20:25-35; Step 2: spray the slurry prepared in step 1 on the ultra-high burning rate Al-Ni film, and dry it in argon protective gas at 120-180° C. for 1.5-2.5 hours to obtain the ultra-high burning rate double-layer ignition sheet.

7. The method for preparing the ultra-high burning rate double-layer ignition sheet according to claim 6, characterized in that: The adhesive is a PVB solution.

8. The method for preparing the ultra-high burning rate double-layer ignition sheet according to any one of claim 7, characterized in that: The ratio of PVB to ethanol in the PVB solution is 1 g:90-120 ml.

9. The method for preparing the ultra-high burning rate double-layer ignition sheet according to claim 8, characterized in that: When preparing the slurry, the mass ratio of the mixture to the PVB solution is 0.9-1.1:

1.

10. Use of the ultra-high burning rate double-layer ignition sheet according to any one of claims 1 to 5 in a thermal battery.

Citation Information

Patent Citations

  • Method for improving safety of ignition paper preparation

    CN109837806A

  • A method to improve the safety of ignition paper preparation

    CN109837806B

  • Thermal battery composite ignition paper and preparation method thereof

    CN113322115A